Manajemen Konflik Antar Mahasiswa Di Sekolah Tinggi Teologi Berasrama: Suatu Tinjauan Konseptual - Krisda Mahdalena Sinaga; Binur Panjaitan (Mitra Sriwijaya: Jurnal Teologi dan Pendidikan Kristen, 2026)
Dormitory life constitutes an essential component in promoting the success of student education. Students come from diverse cultural, familial, personal, intellectual, value-based, and spiritual backgrounds. Such diversity is an inseparable aspect of residential student life. On the one hand, diversity can enrich communal living experiences; on the other hand, it may give rise to interpersonal conflicts. Conflicts that are not managed effectively have the potential to hinder students’ holistic development. This study employs a library research approach to examine conflict management within student dormitories. The findings indicate that interpersonal conflict among students is a common and potential occurrence in dormitory settings due to the diversity of students’ backgrounds. Effective conflict management should be grounded in strong educational philosophical foundations—namely holistic, collaborative, and transformative principles—in order to foster a harmonious residential environment and support students’ comprehensive development. Based on a synthesis of the literature, the collaborative conflict management style emerges as an effective strategy for managing conflicts constructively by generating solutions that accommodate the interests of all parties involved. Furthermore, the collaborative approach is considered the most relevant because it promotes dialogue, cooperation, and the pursuit of mutually beneficial solutions among students. This article contributes practical recommendations for dormitory administrators in building healthy and supportive residential communities.